Entrepreneurs perceived risk and risk-taking behavior in the small-sized creative businesses of tourism sector during COVID-19 pandemic - Agustina, Iin; Bin Ajis, Mohd Naeim; Pradesa, Hafid Aditya (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2021)
The small-sized creative business in the tourism sector has been suffering risks of bankruptcy since the outbreak of coronavirus disease (COVID-19). Drawing on the basic theory of reasoned action, this study aims to investigate entrepreneur risk perceptions affect their risk-taking behavior. This study only focuses on the determinants of risk-taking, with regards to the perspective from an entrepreneurial lens in perceiving business, product, and profit risk during the COVID-19 pandemic. A quantitative approach using a structured questionnaire survey was utilized to attain the study objective. The dataset consists of 177 valid responses by the owner of the small-sized creative business of Indonesias tourism sector (mainly in handicraft and fashion categories). Correlation analysis and partial least square (PLS) modeling were employed to examine the causal relationship between constructs. Our empirical findings revealed that while entrepreneurs' perceived risk on business and product aspects was the most significant aspect that could affect their risk-taking behavior, entrepreneurs' perceived risk on profit aspects have an insignificant influence on their risk-taking behavior. It implies that the higher the level of business and product insecurity perceptions (as long as it can generate profitability and ensure business sustainability), the higher the level of risk-taking of entrepreneurs.